The Cambridge companion to business & human rights law - Bantekas, Ilias 1970-; Stein, Michael Ashley (Cambridge University Press, 2021)
Business and human rights : foundations and linkages / Ilias Bantekas -- Reconciling international human rights with international trade / Francesco Seatzu -- Neo-liberalism, state-capitalism and European ordo-liberalism : why power politics and 'constitutional failures' undermine economic law and human rights / Ernst-Ulrich Petersmann -- Corporate governance and corporate social responsibility / John Paterson -- The role of business in international development and the attainment of the sustainable development goals / Katerina Akestoridi -- The business case for human rights - irrelevant or indispensable? / Dorothee Baumann-Pauly and Lilach Trabelsi -- The UN guiding principles on business and human rights and its predecessors : progress at a snail's pace? / Surya Deva -- The regulatory framework of multinational enterprises / Peter Muchlinski -- The UN global compact and the OECD guidelines on multinational enterprises and their enforcement mechanisms / Andreas Rasche --
Includes bibliographical references and index
Keywords: Corporate Social Responsibility; Menschenrecht; Social responsibility of business / Law and legislation; Human rights